O chapéu como protagonista: uma proposta de sistema produto com foco em chapelaria - Goldim, Samanta dos Santos (Universidade do Vale do Rio dos Sinos, 2019)
This monograph talks about the history of the hat, from its emergence to its evolution over the years, with the main objective of identify the moment when the accessory fell out of use and bring it as a protagonist in a fashion collection. To achieve this goal, were considered the following specific objectives: (I) identify the origin of the hat and analyze its evolution throughout history; (II) analyze the changes in society's consumption behavior throughout the history of fashion, identifying the moment when the hat as an accessory fell into disuse; (III) develop scenarios based on strategic design tools for the positioning of headgear today; (IV) create a contemporary headwear brand; and (V) design a fashion product system, bringing the hat as protagonist. It is a bibliographical and qualitative research, with exploratory character. The data collection techniques used were bibliographic research and interview with two renowned professionals in the area of headgear and costumes. From the information obtained, it was possible to create future scenarios and analyze competing brands. A brand proposal was developed focused on the headgear, as well as its product/service system. The collection consists on ten models of hats inspired by the fauna and flora of Brazil. It is believed that this work may contribute to both the fashion market, the widespread use of the hat and the academic area, since there are not many references on the subject.
Keywords: Chapelaria; História da moda; Evolução do chapéu; Headgear; Fashion history; Hat evolution